The five dimensions of Futures Consciousness - Sanna Ahvenharju; Matti Minkkinen; Fanny Lalot (Elsevier, 2025)
Futures research studies and builds images of possible, probable and preferable futures and paths to such futures. Underlying this eﬀort is human consciousness of futures that is present in everyday anticipatory behaviour and explicit foresight. Futures researchers often aim to increase this consciousness in order to enable decision-making towards more desirable futures. Despite the importance of the concept of Futures Consciousness, and the proliferation of related concepts, there is no commonly used deﬁnition or operationalization that would permit empirical research. This article presents a conceptual model of Futures Consciousness that is based on an integrated review and analysis of the descriptions of future consciousness and its related concepts in literature as well as in the theoretical underpinnings of futures research. The model contains ﬁve dimensions: 1) Time perspective, 2) Agency beliefs, 3) Openness to alternatives, 4) Systems perception and 5) Concern for others. The model provides the basis for further conceptual development and the operationalization of Futures Consciousness, which would enable its use in empirical research.